Galvanic Enhancement for High Pressure Leaching of Chalcopyrite - Kim, Dae Hun; Kim, Hyun Soo; Han, Kyu Sung; Tran, Tam; KIM, Myong Jun (Journal of Mining and Metallurgy, Section B: Metallurgy, 2016)
This study was conducted to evaluate the galvanic enhancement of the pressure oxidation (POX) leaching of a chalcopyrite/chalcocite concentrate, which is believed to take place via a redox reaction. Cu recoveries of >90% could be achieved during POX leaching of this chalcopyrite/chalcocite concentrate at 200o C and 0.7 MPa initial oxygen pressure within 2 h in a pressure reactor lined with titanium, which were 18-28% higher than for the same leaching using the teflon liner. A slow heating time seems to produce more sulphur coating, reducing the leaching performance, yielding much lower Cu recovery when the teflon lining was used, although this does not greatly affect the other case when the reactor was lined with titanium. The introduction of an electronic conductor, in this case the titanium surface, is believed to enhance this redox process, in which the oxidation of copper minerals and sulphur to sulphate at the anodic sites (mineral surface) encountered during POX leaching takes place simultaneously with the reversible oxidation/reduction of the Fe2+/Fe3+ couple and oxygen reduction on titanium.